Fundamentals of airline operations - Meijer, Gert (New York : Routledge, 2020)
"This book provides a general introduction into aviation operations, covering all the relevant elements of this field and the interrelations between them. Numerous books have been written about aviation, but most are written by and for specialists and assume a profound understanding of the fundamentals. This textbook provides the basics for understanding these fundamentals. This book explains how the commercial aviation sector is structured, and how technological, economic and political forces define its development and the prosperity of its players. Aviation Operations have become an important field of expertise. Airlines, airports and aviation suppliers, the players in aviation, need expertise on how aircraft are profitably exploited by connecting airports with the aim to add value to society. This book covers all relevant aspects on how they all do this, including contemporary challenges like capacity constraints and sustainability. This textbook delivers a fundamental basic understanding of the commercial aviation sector at a level ideal for first-year university students but also appropriate and accessible to people already employed within aviation seeking an accurate overview of operations"--
Introduction; PART I The aviation sector 1 Theoretical framework 2 Authorities in aviation 3 Structure of supply 4 Structure of demand 5 Sustainability of aviation; PART II Airports 6 The legal framework of airports 7 Types of airports 8 Airport economic management 9 Aeronautical services at the airport 10 Airport capacity management; PART III Aircraft 11 Aircraft operation 12 Aircraft economics 13 Aircraft supply and MRO; PART IV Airlines 14 Airline management 15 Airline economics 16 Airline planning 17 Airline operations; PART V Epilogue 18 Into the future
OCLC-licensed vendor bibliographic record.
Keywords: Airlines -- Management; Business logistics; Scheduling; Aeronautics, Commercial -- Passenger traffic; TRANSPORTATION / Aviation / Commercial; BUSINESS & ECONOMICS / Industries / Transportation